Effects of Chemical Pretreatments on Physiochemical and Drying Characteristics of Solar-Dried Tomatoe (Lycopersicon esculantum) Slices - Chapagain, M.; Ojha, P.; Karki, R.; Subedi, U.; Shrestha, M.B. (Nepalese Horticulture, 2018)
Abstract available with the full text.